Biology and development of xanthopimpla pedator (hymenoptera: ichneumonidae): pupal endoparasitoid of antheraea mylitta (Lepidoptera: Saturniidae) - Gathalkar, Ganesh B.; Barsagade, Deepak D.; Sen, Avalokiteswar (Annals of the Entomological Society of America, 2017)
The Antheraea mylitta (Drury) (Lepidoptera: Saturniidae) is a commercially important species for the production of tasar silk. However, the Xanthopimpla pedator (F.) (Hymenoptera: Ichneumonidae) is a major pupal endoparasitoid of A. mylitta, which affects the total tasar silk production in India. A gravid female X. pedator parasitizes the pupae of A. mylitta by depositing an egg, which produces a single offspring per host. We studied the development of immature forms of X. pedator by dissecting parasitized pupae of A. mylitta under laboratory conditions at 28-30 degrees C and 40-60% relative humidity. All immature stages of the parasitoid develop within the host in 20-22 d, by devouring the entire pupal content, resulting in dead or seedless cocoons. The total life cycle of X. pedator is completed inside the host pupa and the adult emerges out by rupturing the peduncle end of the cocoon. During development of X. pedator, five preimaginal stages, viz., egg, larval instars, prepupa, pupa, and a pharate adult, were observed. Xanthopimpla pedator passes through five larval instars identified by structural and morphometric variations. These include primary larva (L1), the intermediate larvae (L2-L4), and the finalinstar larva (L5). Biometric study and larval head width permitted the morphological separation of all five larval instars. In the present study, the biology and development of X. pedator inside the pupa of A. mylitta are reported for the first time with detailed photomicrographs. Therefore, the study may enable the information concerning physiological interactions between A. mylitta and its endoparasitoid, X. pedator.

Blends of neem oil based polyesteramide as nanofiber mats to control Culicidae - Konchada, Sravanya; Killi, Naresh; Sayyad, Shahebaz; Gathalkar, Ganesh B.; Gundloori, Rathna V. N. (RSC Advances, 2020)
Mosquitoes act as vectors for several disease-causing microorganisms and pose a threat to mankind by transmitting various diseases. There are different conventional methods to repel or kill these mosquitoes for avoiding susceptibility against infections. However, to overcome the difficulties with conventional methods, new advanced materials are being studied. For the first time, we report developing a nanofiber mat with a controlled release of insecticide to repel or detain the mosquitoes. Briefly, various blend compositions were prepared by manipulating the ratio of neem oil-based polyesteramide (PEA) and polycaprolactone (PCL) immobilized with insecticide, transfluthrin (Tf). The blend solutions were electrospun to get non-woven nanofiber mats, and these nanomaterials were characterized by various spectroscopic techniques to understand their physicochemical properties. The surface morphology was analyzed using environmental scanning electron microscopy (E-SEM), and the diameter of the nanofibers was in the range of 200 to 450 nm. Further, thermal and mechanical properties were evaluated to understand the stability of nanofiber mats. In vitro drug release studies of nanofiber mat PPT-1335 showed controlled and sustained release of Tf, with similar to 35% of Tf released in 24 h. However, a film of the same composition (PPT-1335) showed similar to 5% of Tf release within 24 h. Moreover, in vivo bio-efficacy studies suggested the mortality of mosquitoes was about 50% with PP-133, which was further increased to 100% within 12 h in the presence of Tf (PPT-1335). However, 60% mortality of mosquitoes was observed with the film of PPT-1335. Hence, the nanofiber mat showed better efficacy against mosquitoes as compared to the film of the same composition. The degradation studies under various conditions revealed biocompatibility of the developed nanofiber mats with the ecosystem.